2009
DOI: 10.1177/003335490912400309
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing and Referral to Care in U.S. Hospitals Prior to 2006: Results from a National Survey

Abstract: Hospitals offered HIV testing on the basis of clinical suspicion or risk, but were far from meeting CDC's current recommendation to routinely test all patients aged 13 to 64. Hospital size, teaching status, and geographic location were associated with HIV testing availability and testing practices. Our understanding of current practice identifies opportunities for public health action at the practitioner, organization, and systems levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As a result, HIV screening activity in EDs across the US increased. In 2004, less than 2% of EDs offered HIV screening (32), but by 2009, a quarter of EDs offered some type of organized HIV screening program (33). …”
Section: Discussionmentioning
confidence: 99%
“…As a result, HIV screening activity in EDs across the US increased. In 2004, less than 2% of EDs offered HIV screening (32), but by 2009, a quarter of EDs offered some type of organized HIV screening program (33). …”
Section: Discussionmentioning
confidence: 99%
“…10 Previous research has shown that the teaching status and size of hospitals, as well as the region and type of metropolitan area in which they are located, are associated with the availability of HIV testing in hospitals. 11 However, there are few published data about hospital characteristics that are associated with the adoption of CDC's revised testing recommendations, and existing studies do not consider the impact of external factors, such as state regulations or third-party reimbursement policies, that might influence whether hospitals adopt the testing guidelines. Also unknown is how the screening practices of hospitals that serve larger proportions of low-income and minority patients compare with the practices of other hospitals.…”
mentioning
confidence: 99%
“…4 However, the extent to which HIV screening is being conducted in hospital settings nationally is unknown. Surveys conducted before the 2006 CDC recommendations showed that few hospitals screened patients for HIV outside of labor and delivery 5 and that HIV screening in EDs was uncommon, 6,7 despite evidence of missed opportunities for diagnosis of HIV in health-care settings. [8][9][10] To assess hospital adoption of CDC HIV screening recommendations, we surveyed a sample of American Hospital Association (AHA) member hospitals during 2009-2010.…”
mentioning
confidence: 99%